Giant retroperitoneal dedifferentiated liposarcoma mimicking ovarian cancer: A case report - Akihiro Tani; Yosuke Tarumi; Akiyo Kakibuchi; Kohei Aoyama; Tetsuya Kokabu; Hisashi Kataoka; Kaori Yoriki; Michiko Nagamine; Taisuke Mori (Elsevier, 2022)
Retroperitoneal liposarcoma is a rare tumor, and its dedifferentiated subtype and a larger diameter are associated with a poor prognosis. However, there are few reports of retroperitoneal liposarcomas, both with a dedifferentiated subtype and a diameter of >30 cm. We report a case of a giant retroperitoneal liposarcoma with a dedifferentiated subtype. A 78-year-old woman presented to our hospital with abdominal distension and loss of appetite. Computed tomography and magnetic resonance imaging findings revealed a 35-cm-diameter solid tumor in the peritoneal cavity. CA125 (64.8 U/mL) and HE4 (229.0 pmol/L) were elevated preoperatively raising suspicion for ovarian malignancy. However, intraoperative findings revealed that the tumor originated in the retroperitoneal cavity. Reductive surgery for the tumor and partial resection of the sigmoid colon and left ureter were performed, and pathological examination confirmed a retroperitoneal dedifferentiated liposarcoma. Although her symptoms improved postoperatively, she died 11 months after surgery due to disease progression.